PASAR KEUANGAN PADA MASA RESESI STUDI KASUS PADA PASAR INDONESIA - Sudjana, Nengah (Profit: Jurnal Adminsitrasi Bisnis, 2008)
Financial market uncertainty in developing countries, including Indonesia can be caused by some factors differ with develop country. This paper use descriptive analysis to research and analyze Indonesian financial market in resession era. The analysis showed that Indonesian financial market was determined by nonfundamental factors, such as public policy. The result of this research could be used to elaborate some factors influencing fmancial market that often was ignored in some literatures. Keywords: financial market, window dressing, resession, non-fundamental factor